Orthorexia nervosa: A review of psychosocial risk factors. (1st September 2019) - McComb, Sarah E.; Mills, Jennifer S.
Abstract: Orthorexia nervosa (ON) is a condition described as a pathological obsession with healthy eating. This paper will review the prevalence of ON and how ON is measured. The primary objective is to critically analyze findings on the psychosocial risk factors associated with ON, to consider its relation to other mental disorders, and to offer directions for future research. The key words "orthorexia" and "orthorexia nervosa" were searched in the databases PsycINFO and MEDLINE/PubMed. This paper reviewed peer-reviewed articles published up until December 31st, 2018. Quality assessment was conducted on each study reviewed. Results identified psychometric problems with the most common measure of ON. Gender and self-esteem were generally found to be unrelated to ON. Perfectionism, obsessive-compulsive traits, psychopathology, disordered eating, history of an eating disorder, dieting, poor body image, and drive for thinness were positively associated with greater ON. Findings between ON and the following risk factors were mixed: age, SES, BMI, belonging to a health-related field, exercise engagement, vegetarianism/veganism, body dissatisfaction, and alcohol, tobacco, and drug use. We discuss how the literature on risk factors informs understanding the nature of psychopathology of ON. Strengths and limitations of studies are reviewed and directions for future research are identified. Suggestions are made for more psychometrically valid assessment measures of ON that include questions about impairment, so that ON etiology can be accurately studied.